Theta Modulated Neural Phase Coherence Facilitates Speech Fluency in Adults Who Stutter - Sengupta, Ranit; Yaruss, J. Scott; Loucks, Torrey M.; Gracco, Vincent L.; Pelczarski, Kristin; Nasir, Sazzad M. (Frontiers in Human Neuroscience, 2019)
Adults who stutter (AWS) display altered patterns of neural phase coherence within the speech motor system preceding disfluencies. These altered patterns may distinguish fluent speech episodes from disfluent ones. Phase coherence is relevant to the study of stuttering because it reflects neural communication within brain networks. In this follow-up study, the oscillatory cortical dynamics preceding fluent speech in AWS and AWNS (adults who do not stutter) were examined during a single-word delayed reading task using electroencephalographic (EEG) techniques. Compared to AWNS, fluent speech preparation in AWS was characterized by a decrease in theta-gamma phase coherence and a corresponding increase in theta-beta coherence level. Higher spectral powers in the beta and gamma bands were also observed preceding fluent utterances by AWS. Overall, there was altered neural communication during speech planning in AWS that provides novel evidence for atypical allocation of feedforward control by AWS even before fluent utterances.